Dynamic simulation of the temperature inlet turbine control system for an unfired micro gas turbine in a concentrating solar tower. (August 2018) - Amelio, M.; Pèrez, M. Silva; Ferraro, V.; Rovense, F.; Bova, S.
Abstract: In this work, the dynamic performance of a mass flow regulation system, in a concentrating solar tower plant, with unfired closed micro gas turbine, during clouds transient will be presented. The adjustment system operates with the heliostats field control system, in order to control the temperature inlet turbine. To choose the best configuration, the performance of three heliostats sizes, for four Solar Multiple, has been evaluated. The design of the solar field was carried out by means of Solar Pilot, while the numerical models have been developed in Matlab/Simulink. The results show that a particular configuration is suitable for this purpose.